Chemical Warfare during the Vietnam War: Riot Control Agents in Combat, 1st edition - Ellison, D. Hank (Routledge, 2020)
Chemical Warfare during the Vietnam War documents the use of antipersonnel chemical weapons throughout the Vietnam War, and explores their effectiveness under the wide variety of circumstances in which they were employed. The short, readable account follows the US program as it progressed from a focus on the humanitarian aspects of non-lethal weapons to their use as a means of augmenting and enhancing the lethality of traditional munitions. It also presents the efforts of the North Vietnamese to both counter US chemical operations and to develop a chemical capability of their own.